Les raisons politiques d’un échec éditorial : la traduction française des Œuvres de Mussolini en France, 1935-1939 - Stéphanie Lanfranchi (Laboratoire Italien)
The article presents the history of the French translation of the complete works of Mussolini, published by Flammarion in the last 1930’s. Flammarion’s archives tell us, among other things, how the translator was chosen on Mussolini’s advice, the terms of the contract with the Italian publisher and the author, the number of copies sold every year. They also allow to understand the political and diplomatic implications of such a publishing operation. Born in the favorable context of rapprochement between France and Italy, it directly suffered the consequences of growing disagreements between the two countries after 1935.